Mahasiswi Kesejahteraan Sosial FISIP USU Ajak Siswa Siswi Terbuka Kepada Orang Tua Melalui Agenda Harian - Angelica Patricia; Bengkel Ginting; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Field Work Practice is a manifestation of students in applying the knowledge gained when attending lectures so that it aims to improve students' skills in developing mindsets, expressing ideas, and gaining insights to become a skilled and qualified workforce. Field Work Practice (PKL) is also a form of community service in accordance with the Tri Dharma of Higher Education. Community service carried out in the field of education is a process that aims to advance the welfare of the community in accordance with Law No. 10 of 2019 concerning Social Welfare. Social intervention methods in individuals are basically related to efforts to improve or improve the social functioning of individuals. Practice follows one of the Merdeka Belajar – Kampus Merdeka (MBKM) programs, namely the Teaching Campus Program. In this community service activity, the practice carries out its service at UPT SD Negeri 060933. The practice of paying attention to the needs of the school is an innovative activity in improving communication between children and parents. Practice carrying out mini projects as a process of analyzing and solving client problems. If the mini project is successful, the needs of students will be achieved.